2010
DOI: 10.1111/j.1365-2133.2010.10077.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in patients with psoriasis: increased prevalence, an unmet need, and a chance to intervene

Abstract: We present the largest survey of ED in patients with skin disease, and the first to posit the potential link between psoriasis, ED and atherosclerosis. We suggest that an assessment of sexual function should be part of the routine holistic care provided for dermatology outpatients, and highlight the need to screen for cardiovascular risk factors in those with documented ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 31 publications
(101 reference statements)
3
50
1
2
Order By: Relevance
“…In our study, the prevalence of ED in both psoriasis patients and healthy subjects is in line with previous reports, indicating high levels of ED in psoriasis patients (Chung et al, 2012;Goulding et al, 2011;Martin-Morales et al, 2001;Sierra et al, 2012). Accordingly, the population of patients with moderate to severe psoriasis may be considered a high-risk population for ED.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the prevalence of ED in both psoriasis patients and healthy subjects is in line with previous reports, indicating high levels of ED in psoriasis patients (Chung et al, 2012;Goulding et al, 2011;Martin-Morales et al, 2001;Sierra et al, 2012). Accordingly, the population of patients with moderate to severe psoriasis may be considered a high-risk population for ED.…”
Section: Discussionsupporting
confidence: 92%
“…Inourstudy,weobserved that smoking is involved in a greater risk of ED and is more prevalent among moderate to severe psoriasis patients. Other studies have found a significant association between arterial hypertension, dyslipidemia or diabetes mellitus and ED in patients with psoriasis (Table 1) (Cabete et al, 2014;Chen et al, 2013;Chung et al, 2012;Goulding et al, 2011). These factors, such as smoking, anxiety, and depression, are more prevalent among psoriasis patients than in the general population and are also associated with a higher risk of ED (Corona, Mannucci, Forti, & Maggi, 2009;Martin-Morales et al, 2001;Nunes, Labazi, & Webb, 2012).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The impact of depression on sexual dysfunction in psoriatic patients is controversial (non-related/positive correlation). MTX and retinoids have been were also found to be related with loss of libido and erectile dysfunction 69,70 .…”
Section: Erectile Dysfunctionmentioning
confidence: 99%
“…propose that the psychologic burden associated with psoriasis is a stronger component of psoriasis burden than physical aspects of the disease, such as disease severity, location or duration. On a promising note, patient complaints of psoriasis‐related social and sexual difficulties have significantly decreased since the advent of highly efficacious biologic therapeutics for the treatment of psoriasis 16, 17, 18…”
Section: Introductionmentioning
confidence: 99%